Pola Distribusi Hujan Jam-Jaman Pada Stasiun Hujan Pasar Kampar - Adiyka Fasanovri Asfa; Yohanna Lilis Handayani; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
In the analysis of flood hydrograph to input of designed rainfall, usually rainfall parameters like as duration and rainfall distribution pattern were not available, but actually the case is very important for analysis. rainfall distribution pattern can be seen in two ways, the first is observation of rainfall events using automatic rainfall recorder and rainfall distribution model.The study using rainfall data from rainfall stations Pasar Kampar, Kampar Regency. The research was done by comparing the rainfall distribution pattern of hourly from observations method with distribution pattern of hourly using rainfall distribution model. Rainfall distribution model used is the Alternating Block Method (ABM), Modified Mononobe, and Tadashi Tanimoto.The analysis showed that rainfall in station Pasar Kampar was dominated by three hour rainfall events. Distribution of rainfall three to seven hours, rainfall distribution model ABM giving out largest deviation compared with distribution model Modified Mononobe, and for the distribution of rainfall eight hours the smallest deviation given by rainfall distribution model. Tadashi Tanimoto.Keywords: rainfall duration, rainfall distribution pattern, rainfall distribution model.